Study to assess sub-foveal choroidal thickness in patients of preeclampsia through spectral domain optical coherence tomography - Lalwani, Astha; Rastogi, Priye Suman; Najam, Rehana; Chander, Ashish (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Aim of the study was to assess sub-foveal choroidal thickness (SFCT) in preeclamptic patients by SD ocular coherence tomography (SD-OCT) and correlate its changes with severity of preeclampsia. Method: This case control, observational study, conducted in department of ophthalmology in association with department of obstetrics and gynaecology. The subjects were split into two groups: study and control. Study group was further divided in to 2 groups i.e., group A (Patients with preeclampsia) and group B (Pregnant females without preeclampsia). Control group (Group C) of non-pregnant females of similar age group. Total 100 patients were taken in each group. Subjects from both study and control groups were subjected to SD-OCT and mean choroidal thickness of both eyes was noted. Data was noted and comparison of 3 groups was done. Results: Baseline characters viz, age, period of gestation, and parity was comparable among all the groups as p>0.05. Mean arterial pressure (MAP) was 102.72±9.81 and 84.56±7.83 in group A and B respectively with statistically significant difference as p<0.01. Following a post hoc analysis, it was discovered that the SFCT of the healthy pregnancy group did not differ substantially from that of the control group, however the SFCT of the pre-eclampsia group was significantly higher than that of the control and healthy pregnancy groups. Conclusions: Pre-eclampsia causes a greater increase in sub-foveal choroidal thickness than normal pregnancy or non-pregnant women. It has the potential to be used as a predictor or marker of pre-eclampsia severity.